2012
DOI: 10.1016/j.ijinfomgt.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Empowering teams through social network ties

Abstract: ABSTRACT:Effective teamwork and knowledge coordination are becoming increasingly important for all kinds of organizations given the growing use of teams to tackle competitive challenges and sustain competitive advantage. In this study, we develop and validate a model of how two types of social network ties -expressive and instrumental -contribute first to three dimensions of a transactive memory system (TMS) -specialization, credibility and coordination within teams -and subsequently to team efficacy and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 95 publications
3
72
1
1
Order By: Relevance
“…It will be formed between the groups with different background, professional fields and in different cultural environment [12]. Gibbons proposed that in the workplace, the relationship between the peers is mostly the overlap of instrumental ties and expressive ties [13].…”
Section: B the Social Network Relationship And Interpersonal Trustmentioning
confidence: 99%
“…It will be formed between the groups with different background, professional fields and in different cultural environment [12]. Gibbons proposed that in the workplace, the relationship between the peers is mostly the overlap of instrumental ties and expressive ties [13].…”
Section: B the Social Network Relationship And Interpersonal Trustmentioning
confidence: 99%
“…Density varies between 0 and 1, so that a contributor who communicated on all tasks would have a density of 1, while one with no interaction would have a density of 0. Individuals involved in highly dense communication network segments have been shown to dominate coordination and collective action [37], and are seen as most important to their teams [38]. We created a baseline using a similar approach to that used by Crowston et al [39], and selected all practitioners whose density measure was ≥ 0.33 (i.e., they communicated on a third or more of their teams' project tasks), and labeled them as top contributors or 'core developers'.…”
Section: Procedures and Metricsmentioning
confidence: 99%
“…It is further expected the research will have theoretical and practical implications. (Wegner, 1987), and was introduced to explain intimate couples' ability to negotiate knowledge when faced with dis-98 ruptions in their group memory (Wegner, 1987;Zhong et al, 2012). Transactive memory exists as a collective system of 99 knowledge, and it entails each individual's memory system as well as the details of the interactions during communication 100 (Wegner, 1987).…”
mentioning
confidence: 99%
“…The results of Li and Huang (2013) suggested that TMS reinforces exploitative and 118 exploratory learning in the context of team learning. According to Zhong et al (2012), TMS is an effective knowledge-119 processing technique and can lead to improved team outcomes. They examined the relationship between TMS and team out-120 comes and the results showed that TMS had an impact on team outcomes through team efficacy.…”
mentioning
confidence: 99%